"If Ever Saints Wept and Hell Rejoiced, It Must Have Been Over the Passage of That Law": The 1850 Fugitive Slave Act in Detroit River Borderland Newspapers, 1851-1852. Issue 1 (2nd January 2023) - Lindner, Anna E.; Fuhlhage, Michael; Frazier, D. T.; Neal, Keena S.
ABSTRACT: The passage of the Fugitive Slave Act in 1850 raised the stakes for antislavery Whites and people of African descent in the United States by making resistance to slave catchers a federal crime. This study uses historical theme analysis to examine the rhetoric employed by newspapers in the Detroit River Borderland, which connected Michigan to Canada West, to promote or resist the Fugitive Slave Act from 1851 to 1852. While the Canada-based Voice of the Fugitive, edited by the formerly enslaved Henry Bibb, and the Michigan Christian Herald, a Baptist antislavery newspaper in Detroit, argued that the Fugitive Slave Act was unconstitutional and immoral, the proslavery Detroit Free Press supported the Act. These differing stances evince the divisiveness of the Fugitive Slave Act, which had been developed as a compromise measure a decade before the US was divided by civil war.